1999
DOI: 10.1515/bc.1999.026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transcription Factor MTF-1 from the Japanese Pufferfish (<I>Fugu rubripes</I>) Reveals Evolutionary Conservation of Heavy Metal Stress Response

Abstract: The pufferfish Fugu rubripes was recently introduced as a new model organism for genomic studies, since it contains a full set of vertebrate genes but only 13% as much DNA as a mammal. Fugu genes tend to be smaller and densely spaced due to shortening of introns and intergenic spacers. We isolated the Fugu gene for the metal-responsive transcription factor MTF-1 (MTF1), a mediator of heavy metal regulation and oxidative stress response previously characterized in mammals. In addition, most of the cDNA sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Note that in the NES region, typical mammals are more closely related to birds and reptiles than to rodents (see also (Georgiev et al 2014 )). The MTF-1s of the animals have not been functionally tested, except those of slow worm (Georgiev et al 2014 ), and fugu (Auf der Maur et al 1999 ), both of which functioned very well in our standard reporter assay (for zebrafish, see also Cheuk ( 2008 )). The extensive alterations in the rabbit (Oryctolagus) and the two lysines replacing leucine and threonine in opossum (Monodelphis) might be worth a further investigation; both of them are relatively short-lived, rapidly multiplying species.…”
Section: Resultsmentioning
confidence: 99%
“…Note that in the NES region, typical mammals are more closely related to birds and reptiles than to rodents (see also (Georgiev et al 2014 )). The MTF-1s of the animals have not been functionally tested, except those of slow worm (Georgiev et al 2014 ), and fugu (Auf der Maur et al 1999 ), both of which functioned very well in our standard reporter assay (for zebrafish, see also Cheuk ( 2008 )). The extensive alterations in the rabbit (Oryctolagus) and the two lysines replacing leucine and threonine in opossum (Monodelphis) might be worth a further investigation; both of them are relatively short-lived, rapidly multiplying species.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have described complete MTF-1 transcripts in two other fish species, the pufferfish ( Takifugu rubripes ) and tilapia ( Tilapia aurea×Tilapia nilotica ) [4, 31], which encode for 780 and 811 amino acid proteins, respectively. Using the Takifugu MTF-1 sequence as a guide, we were able to identify a missing exon and amplify a full zebrafish MTF-1 transcript containing an open reading frame that encodes for a 722 amino acid protein (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…The application of a transgenic zebrafish expressing a dominant-negative bone morphogenetic protein (Bmp) under control of a heat shock-inducible promoter [29, 30] is validation of such an approach. Previous research has identified a zebrafish MTF-1 homologue that is significantly shorter than the typical vertebrate MTF-1 and missing the cysteine-rich motif [5]; although complete MTF-1 transcripts have been described other fish species [4, 31]. Therefore in our initial effort we sought to investigate the functional diversity of MTF-1 transcripts in zebrafish, followed by an investigation of the in vivo efficacy of the dominant-negative MTF-1 by microinjection of in vitro transcribed mRNA in zebrafish embryos as a precursor to the development of a transgenic zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…MTF-1 has been identified and at least partially characterized from human, mouse (14), pufferfish Fugu rubripes (15), zebrafish Danio rerio (16,17) and Drosophila (18). Human and mouse MTF-1 as well as the Drosophila homolog, termed dMTF-1, contain multiple functional domains, including a highly conserved zinc-finger domain that recognizes the cognate DNA sequence termed metal response element (MRE) (8).…”
Section: Introductionmentioning
confidence: 99%